IMPLIKASI GURU DAN SEKOLAH DALAM PENGUATAN PENDIDIKAN KARAKTER SISWA KELAS V - Taufik Tri Risqi; Dina Prasetyowati; Agnita Siska Pramadyahsari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is motivated by deviations by students that occur in the school environment. Teacher and the school have a certain strategy in dealing with this. This study describes the efforts of teacher and school policies in Strengthening Character Education (PPK) for fifth grade students. The research method used is descriptive qualitative research. Data collection techniques in the form of observation, interviews, documentation, and field notes. Data analysis in this study was carried out after being in the field. Data analysis uses the opinion of Miles and Huberman. The results of this study are: (1) class V teacher in PPK act as role models, inspirers, motivators, dynamists, and evaluators for students, (2) school policy towards grade V PPK is carried out based on the preparation of school rules, socialization of school rules, and enforcement of school rules (3) PPK in grade V is carried out on the basis of PPK values, namely religious, nationalist, independent, mutual cooperation, and integrity.